PENGARUH PERAN ORANG TUA TERHADAP KECERDASAN SPIRITUAL ANAK USIA 5-6 TAHUN - Gusti Puspita Sari; Fadullah; Ratih Kusumawardani (STKIP Subang, 2023)
This study aims to determine the influence of the role of parents on the spiritual intelligence of children aged 5-6 years in the neighborhood, RT.04/11 Kel. Benconngan-Tangerang. The research used by the researcher is a quantitative research with the type of Ex-post Facto research with a sample of 16 parents who are in the neighborhood of RT.04/11. The results of the correlation coefficient between the role of parents and the spiritual intelligence of children aged 5-6 years show a number of 0.615, which means it has a very high level of relationship because it is in the interval > 0.75 to 0.99. Which means that the role of parents on children's spiritual intelligence with the results of the correlation coefficient table can be seen from rcount < rtable which is 0.615 < 0.497 which means it has a strong level of relationship, then H1 is accepted because the value in sig (2-tailed) is 0.011 < 0.05, so it can be said that the hypothesis H0 is rejected and H1 is accepted. This means that there is a significant influence on the role of parents on the spiritual intelligence of children aged 5-6 years in the 010 community, Bencongan-Tangerang village.